Towards the sociology of truth - Moore, Rob, 1946- (Continuum studies in education., 2009)
This title examines a series of inter-related problems associated with the nature of knowledge, how it is produced within intellectual fields and the implications for the transmission of knowledge in the classroom. This innovative monograph is concerned with a set of inter-related problems associated with the nature of knowledge, how it is produced within intellectual fields and the implications of those things for education and the transmission of knowledge in the classroom. It covers issues in the sociology of knowledge, the educational system and policy, social differences in educational at.